Pengawasan Terhadap Perbaikan Infrastruktur Pada Dinas Pekerjaan Umum Penataan Ruang (PUPR) Kabupaten Sukabumi - Abdillah, Mohammad Ichsan; Appandi, Karlina; Meliani, Mila; Amara, Piranti; Darmawan, Ivan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Infrastructure improvements at the Public Works and Spatial Planning (PUPR) Department of Sukabumi Regency need to be prioritized to ensure quality, timeliness and efficiency in implementing building projects. This policy focuses on employee training, material quality, and work suitability based on previously established objectives and technical specifications. Through concise and comprehensive planning, it is hoped that it will be able to reduce bureaucracy, increase accountability and increase transparency at every stage of infrastructure improvement. The results of this research also provide valuable information for future research and project implementation, so that infrastructure development in Sukabumi Regency can run smoothly and efficiently and provide maximum benefits to the general public. The data collection method used in this research is library research, by reading, recording and processing data from journals, articles and relevant documents. The results of this research are that there are two types of supervision in infrastructure repairs, namely preventive and representative at the Public Works and Spatial Planning (PUPR) Department of Sukabumi Regency.